(untitled) (KASBIT Business Journal, 2023)
Internet accessibility has changed consumers’ attitudes and behaviors regarding searching and sharing information about goods and services. These interactions generate eWOM communications affecting trust, brand loyalty, and purchase intentions. Given the significance of eWOM, the study has developed a model that has examined seven relationships, including one moderating. The study recruited six enumerators who intercepted 415 respondents in the targeted malls. Of this total, 390 responded. The study used smart PLS for data analysis. EWOM affects trust, purchase intention, and brand loyalty. The study also found that brand loyalty and trust promote purchase intentions. Homophily also affects eWOM. In contrast to past literature, the study found an "insignificant linkage between information quality and trust." We also found the "moderating effect of sense of power on information quality and trust." The contribution of the study is as follows. Most studies have used trust and loyalty as antecedents to eWOM. We have used trust and loyalty as consequences of eWOM, on which a few studies are available. The literature documents inconsistent results on the "effect of eWOM on trust and loyalty" and (ii) the effect of "homophily on eWOM."